2022
DOI: 10.46281/ijafr.v10i1.1649
|View full text |Cite
|
Sign up to set email alerts
|

Potential Sub-Topics and Trend Topics in Financial Literacy: A Bibliometric Analysis

Abstract: This study identifies the potential sub-topics and trend-topics in the financial literacy field through bibliometric analysis using a web-based application, Biblioshiny, on a sample of 787 documents retrieved from Web of Science database by Clarivate Analytics for the timespan 2001–2021 with the keyword “financial literacy”. The study reveals that the numbers of publications are increasing substantially with time. The results show that the term financial literacy is crucially associated with many keywords that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Studies on the effects of financial literacy and studies on gender differences in financial literacy (FL) have indeed been identified as significant trend topics for the 2020-2021 period (Rani and Goyal, 2022). This study also revealed that India had a very low number of publications in the area of women's financial literacy, despite the growth in annual scientific output and international trends in this field.…”
Section: Final Considerationsmentioning
confidence: 76%
See 1 more Smart Citation
“…Studies on the effects of financial literacy and studies on gender differences in financial literacy (FL) have indeed been identified as significant trend topics for the 2020-2021 period (Rani and Goyal, 2022). This study also revealed that India had a very low number of publications in the area of women's financial literacy, despite the growth in annual scientific output and international trends in this field.…”
Section: Final Considerationsmentioning
confidence: 76%
“…Research on the benefits of financial knowledge and studies on gender differences in financial literacy (FL) has indeed been identified as significant popular subjects for the 2020-2021 period (Rani and Goyal, 2022). Bibliometric analysis was necessary to detect possible subtopics and trending topics related to women's financial literacy.…”
mentioning
confidence: 99%
“…Some literature states that literacy categories include finance, information, mathematics and science, media, digital, and technology [30][31][32]. Many bibliometric analysis literature has studied financial literacy [33][34][35][36][37]. Many bibliometric analysis reports have also studied information literacy [38][39][40][41][42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%